Resistance to change and teaching performance in educators of an educational institution - Merino Auccahuasi, Bertha Lucía (2019)
Objective. To establish the relationship between resistance to change level and teaching performance level. Methods. An observational, prospective, cross-sectional, correlational study was carried out at Educational Institution La Inmaculada Concepción de Huanuco, during the 2018 period, comprised of 32 teachers. Instrument used was the resistance to change questionnaire and the teaching performance questionnaire. Data analysis consisted of Spearman’s Rho correlation test. Results. 75 % (24 teachers) had a low level of resistance to change and 90.6 % (29 teachers) showed a high level of teaching performance. On the other hand, a significant relationship was found between resistance to change and teaching performance, with p <= 0.000. And a significant relationship was found between teaching performance and resistance to change dimensions such as inertia (p <= 0.003), participation (p <= 0.000), negotiation (p <= 0.030) and coercion (p <= 0.012). Conclusion. Resistance to change and teaching performance of educators of the Educational Institution La Inmaculada Concepción de Huanuco have a statistically negative correlation.